Two-stage synthesis of control system by the network operator method - A I Diveev; E Yu Shmalko (RUDN Journal of Engineering Research, 2015)
The paper focuses on the problem of control system synthesis and a numerical method of the network operator is proposed to search a solution. Apart from a well-known approach when the stated control synthesis problem is solved directly by the method of network operator considering given criteria and terminal conditions, the present paper describes a two-stage synthesis. The first stage is supposed to solve numerically a set of optimal control tasks for different initial values from some given space. The second stage makes an approximation of the previously received optimal trajectories by means of the network operator. An example illustrates the two-stage synthesis of a control system for a spaceship descent to the Moon.